Chemical Bonding in Silicon Carbonyl Complexes. Issue 41 (1st May 2021) - Sergeieva, Tetiana; Mandal, Debdeep; Andrada, Diego M.
Abstract: Although silylene‐carbonyl complexes are known for decades, only recently isolable examples have been accomplished. In this work, the bonding situation is re‐evaluated to explain the origins of their remarkable stability within the Kohn‐Sham molecular orbital theory framework. It is shown that the chemical bond can be understood as CO interaction with the silylene via a donor‐acceptor interaction: a σ ‐donation from the σ CO into the empty p‐ orbital of silicon, and a π ‐back donation from the sp 2 lone pair of silicon into the π*CO antibonding orbitals. Notably, it was established that the driving force behind the surprisingly stable Si−CO compounds, however, is another π‐back donation from a perpendicular bonding R−Si σ ‐orbital into the π*CO antibonding orbitals. Consequently, the pyramidalization of the central silicon atom cannot be associated with the strength of the π ‐back donation, in sharp contrast to the established chemical bonding model. Considering this additional bonding interaction not only shed light on the bonding situation, but is also an indispensable key for broadening the scope of silylene‐carbonyl chemistry. Abstract : Revisiting the chemical bond on silylene‐carbonyl species reveals a donor‐acceptor interaction between the CO and the silylene. The bonding can be conventionally understood as a σ‐donation from the σCO into the empty p‐orbital of silicon, and a π‐back donation from the sp 2 lone pair of silicon into the π*CO antibonding orbitals. Nonetheless, an unrecognized π‐back‐donation from the R−Si σ‐orbital into the π*CO antibonding orbital faithfully explains the relationship between structure and stability.